2020
DOI: 10.1371/journal.pone.0240513
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity of white matter as a biomarker of cognitive decline in Alzheimer’s disease

Abstract: In vivo functional changes in white matter during the progression of Alzheimer's disease (AD) have not been previously reported. Our objectives are to measure changes in white matter functional connectivity (FC) in an elderly population undergoing cognitive decline as AD develops, to establish their relationship to neuropsychological scores of cognitive abilities, and to assess the performance in prediction of AD using white matter FC measures as features. Methods Analyses were conducted using resting state fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…Accordingly, in this study we extend our previous analyses (19, 21, 22) to a large cohort of patients with schizophrenia and healthy controls on both spontaneous signal during a resting state and activated signal during a spatial working memory task in order to: 1) quantitatively characterize the alterations of FC in WM affected by schizophrenia; 2) explore associations between FC in WM and cognitive functioning across the cohort; 3) further determine whether the FC alterations at WM and cognitive associates detected in schizophrenia are changed by cognitive functional loading.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Accordingly, in this study we extend our previous analyses (19, 21, 22) to a large cohort of patients with schizophrenia and healthy controls on both spontaneous signal during a resting state and activated signal during a spatial working memory task in order to: 1) quantitatively characterize the alterations of FC in WM affected by schizophrenia; 2) explore associations between FC in WM and cognitive functioning across the cohort; 3) further determine whether the FC alterations at WM and cognitive associates detected in schizophrenia are changed by cognitive functional loading.…”
Section: Introductionsupporting
confidence: 80%
“…Our recent work has shown that BOLD signals from WM bundles correlate with those from specific GM regions to which they connect (19, 20). Based on this correlation, we derived a WM-centered FC analysis approach and revealed that the FC at specific WM bundles declined and associated with cognitive scores in Alzheimer’s disease during resting state (21, 22).…”
Section: Introductionmentioning
confidence: 99%
“…In a resting state, the BOLD signals from white matter regions show correlations with other white and grey matter areas in a manner similar to the correlations used to infer functional connectivity between cortical volumes 21 . We, therefore, constructed the resting state matrices showing the correlations between each pair of the 80 ICs for each entire component as well as only the SP and DP portions respectively.…”
Section: Resultsmentioning
confidence: 85%
“…As the WM structural alterations have characterized many brain disorders, researchers have further explored the functional anomaly within WM during rest, such as schizophrenia ( Jiang et al, 2019 ), Parkinson’s disease ( Ji et al, 2019 ), and pontine strokes ( Wang et al, 2019 ). However, few studies have investigated the abnormal homotopic functional connectivity within WM (WM-HFC) in patients within the brain ( Zhao et al, 2019 ; Gao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%